Immunogenic tumor cell death induced by chemoradiotherapy: molecular mechanisms and a clinical translation - Kono, K (Nature Publishing Group, 2013)
Chemoradiotherapy can induce immunogenic cell death, triggering danger signals such as high-mobility group box 1 protein, and resulting in T-cell immunity. This concept can potentially be harnessed for clinical therapy to enhance tumor-specific immunity. There is however limited information to translate this theory directly in a clinical setting. In this review, we will discuss and summarize molecular and cellular mechanisms underlying immunogenic tumor cell death induced by chemoradiotherapy, with emphasis on a clinical translation.